Pengaruh Profitabilitas, Ukuran Perusahaan, Umur Perusahaan, dan Leverage Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan - Damayanti, Ni Komang Sri; Sudiana, I Wayan; Hutnaleontina, Putu Nuniek (UNHI Press, 2025)
Timeliness in preparing and reporting financial statements for each period is a demand for companies that go public. Submission of financial reports is a signal for investors and interested parties in assessing the company's condition. The purpose of this study was to examine the effect of profitability, company size, company age, and leverage on the timeliness of submitting financial reports of non-primary consumer goods companies listed on the Indonesia Stock Exchange. The population used in this study was 142 non-primary consumer goods companies listed on the IDX, with a purposive sampling method obtained a sample of 108 companies with 3 years of observation; the sample data used was 324 data. The data was analyzed using logistic linear analysis. The results of the analysis show that profitability, company size, company age and leverage has no effect on the timeliness of submitting company financial reports. It is recommended that companies continue to submit financial reports on time, considering that financial reports are very important for investors and other stakeholders who want to invest in the company, so that with timely submission, parties with an interest in the company's financial statements can quickly find out the company's condition before deciding to invest.